Optimising Methylene Blue Removal Using Sago Effluent Activated Carbon : A Response Surface Methodology Study - Zainab, Ngaini; Nur Aqilah, Makshut; Nurul Iwani, Mahmut; NORAQILAH, MOHD ADZMI; NURLIDZA, ARSAT; ABIGAIL VANESSA, ZIEM (UMT Press, 2025)
Eliminating effluent-containing dyes into the environment urges for eco-friendly and practical solutions. In this work, sago effluent biomass (SEB) and sago effluent activated carbon (SEAC) were developed as inexpensive and efficient adsorbents. The SEAC was pyrolysed and chemically activated using sodium hydroxide (NaOH). The characterisation and physicochemical properties of SEB and SEAC were analysed. The efficiency of SEB and SEAC for methylene blue (MB) removal was studied at varying initial solution concentrations (2-10 mg/L) and contact times (0-30 min). SEAC exhibits a large pore opening (11.17 μm) compared with SEB (0.21 μm). The total surface area was also increased from 8.04 m2/g (SEB) to 78.863 m2/g in SEAC. Response surface methodology (RSM) analysis showed SEAC at an initial concentration of 10 mg/L and a contact period of 60 min has obtained a maximum removal effectiveness of 92.69% for MB at pH 6. The adsorption of SEB and SEAC both best fit the Langmuir model. SEB had an R² value of 0.9919, while SEAC had an R² value of 0.9225 and an adsorption capacity of 0.9013 mg/g. Sludge-activated carbon derived from sago effluent is an effective adsorbent for removing MB from aqueous environments. Overall, the high surface area and porous structure make it a sustainable solution for mitigating pollution from sago processing industries.